Genes Encoding Potential Molecular Mimicry Proteins as the Specific Targets for Detecting Bursaphelenchus xylophilus in PCR and Loop-Mediated Isothermal Amplification Assays - Meng, Fanli; Liu, Zhenkai; Li, Yongxia; Zhang, Xingyao (Frontiers in Plant Science, 2022)
The introduction of the pine wood nematode (Bursaphelenchus xylophilus) to new areas has affected the international forestry industry because this pathogen causes pine wilt disease. Therefore, methods for the accurate and reliable detection of B. xylophilus are essential for controlling and managing this pest. The PCR and LAMP techniques developed in this study involve species-specific primer sets targeting B. xylophilus genes encoding potential molecular mimicry proteins (Bx-tlp-1, Bx-tlp-2, and Bx-cpi), which are associated with pathogenicity. The PCR and LAMP results revealed that the primers were specific for B. xylophilus Bx-tlp-1, Bx-tlp-2, and Bx-cpi. Moreover, our LAMP assay targeting Bx-tlp-1 conducted at 63 °C detected B. xylophilus within 20 min and B. xylophilus from Monochamus alternatus or M. saltuarius within 30 min. The lower limits of detection for the LAMP and PCR assays were 10 pg and 10 ng genomic DNA, respectively, implying these assays may be useful for the rapid detection of B. xylophilus in pine forests. Designing primers specific for Bx-tlp-1, Bx-tlp-2, and Bx-cpi enabled the relatively rapid detection of B. xylophilus isolates as well as M. alternatus or M. saltuarius carrying B. xylophilus. These primers, which were designed following a thorough functional analysis of key B. xylophilus pathogenicity-related genes, may be useful for developing improved assays for the early diagnosis and prevention of pine wilt disease.